2017
DOI: 10.1002/hon.2487
|View full text |Cite
|
Sign up to set email alerts
|

Relapse in stage I(E) diffuse large B‐cell lymphoma

Abstract: Despite a general favourable outcome in limited stage diffuse large B‐cell lymphoma (DLBCL), relapses occur in about 10 to 20% of patients. Prognostic models only partially identify patients at risk for relapse. Moreover, it is not known whether the outcome after such a relapse is similar to the outcome after relapse in advanced stages. From January 2004 through December 2012, all newly diagnosed patients with stage I(E) DLBCL were retrospectively analysed from 2 clinical databases to investigate the relapse p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 24 publications
2
10
0
Order By: Relevance
“…The most common sites as expected were bone, stomach, and testes. 2,3,19 The outcome of the whole series was excellent with an OS at 5 years of 94% similar to other rituximab era studies. 13 The findings that extranodal involvement was associated with worse survival are in agreement with previous reports of stage I DLBCL in the pre-rituximab era.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The most common sites as expected were bone, stomach, and testes. 2,3,19 The outcome of the whole series was excellent with an OS at 5 years of 94% similar to other rituximab era studies. 13 The findings that extranodal involvement was associated with worse survival are in agreement with previous reports of stage I DLBCL in the pre-rituximab era.…”
Section: Discussionsupporting
confidence: 78%
“…In accordance with previous population-based reports, extranodal DLBCL accounted for 66% of all stage I in our series. 2,3,19 These numbers are higher compared with recent series of limited-stage DLBCL, probably because they also included patients with stage II. The most common sites as expected were bone, stomach, and testes.…”
Section: Discussionmentioning
confidence: 77%
“…The current study also showed that disease stage is not a significant predictor for RR‐RCHOP in DLBCL patients [odds ratio = 1.455 (0.442‐4.793), P = .538]. An earlier study reported a drug therapeutic failure of 15% among patients with stage l of DLBCL disease; and one‐third of them had metastasis of disease to central nervous system 35 . Oki et al 2014’s study on double hit lymphoma patients also showed that there was no significant difference in PFS [OR:1.44, 95% CI (0.76‐2.71), P = .262], overall survival [OR = 1.58, 95% CI (0.78‐3.20), P = .201] and failure to achieve CR [OR = 1.27, 95% CI (0.48‐3.36), P = .628] between advanced disease stage group and early disease stage group 36 .…”
Section: Discussionsupporting
confidence: 53%
“…Glucocorticoid-induced osteoporosis (GIOP) is a is frequently seen in clinics. Systemic metabolic osteopathy characterized by decreased bone strength, increased risk of fracture and bone brittleness may lead to high incidence of serious bone pain, osteonecrosis, joint surface collapse and arthritis which seriously affect standard of health [2].…”
Section: Introductionmentioning
confidence: 99%